Adaptabilitas budaya Gen Z Surakarta: cultural intelligence, value congruence, and attitude toward culture in workplace.: Adaptabilitas budaya Gen Z Surakarta: cultural intelligence, value congruence, and attitude toward culture in workplace. - Adam Sasando; Ahmad Faris Bin Alias (Universitas Duta Bangsa Surakarta, 2024)
This study aims to analyze the influence of Cultural Intelligence, Value Congruence, and Attitude Toward Culture on Cultural Adaptability in Generation Z in Surakarta City. The approach used is quantitative descriptive with data analysis techniques using PLS-SEM through SmartPLS 3.0 software. The sample in this study amounted to 120 respondents who are part of the Gen Z population. The results of the study indicate that Attitude Toward Culture and Value Congruence have a positive and significant influence on Cultural Adaptability. Meanwhile, Cultural Intelligence does not have a significant effect. The R Square value of 0.650 indicates that the model has strong predictive ability. The model is also declared feasible to use based on the results of the SRMR and Q Square tests. These findings confirm that attitudes towards culture and equality values ??are important factors in increasing Generation Z's adaptability to cultural diversity in the workplace.